Pseudoaneurysm of the sural artery: a rare complication of lower limb angioplasty. Issue 2 (May 2014) - Aziz, Abdul; Green, Allan; Maskova, Jana; Rajagopalan, Sriram; Bachoo, Paul
Introduction: Percutaneous transluminal angioplasty (PTA) is a common therapeutic option for the treatment of peripheral vascular disease. Pseudoaneurysm at the puncture site is a well-documented complication in patients. Case presentation: This case report describes a patient who presented to hospital several days following a left superficial femoral and popliteal artery PTA with lower limb pain and swelling. The working diagnosis included a deep vein thrombosis based on the Wells criteria. However, a combination of a duplex scan and computed tomography angiography confirmed a clinically rare occurrence of pseudoaneurysm of the sural artery, a branch of the popliteal artery. This was managed successfully with a thrombin injection, leading to complete resolution of the patient's symptoms. Conclusion: This case highlights the importance of the technical aspects of performing a PTA. We believe that the guide-wire position was not confirmed to be completely in the popliteal artery upon inflation of the balloon.